Hybrid carbon/glass fiber reinforced polymer; a frontier material for aerospace industry : a review on mechanical properties enhancement - Ab Ghani, Ahmad Fuad; Ngatiman, Nor Azazi; Jumaidin, Ridhwan; Dhar Malingam, Sivakumar; Abdul Munir, Fudhail; Ranom, Rahifa (Penerbit Universiti Malaysia Pahang, 2021)
Composite is the combination of two or more materials that differ in properties and composition to form unique properties. This paper reported the deformation of hybrid composite under tensile, shear and flexural loading. This review provides insight and state of the art for mechanics of composites that provides underlying theory for understanding the deformation and behaviour for the hybrid composite under various loading conditions. This paper also discusses mechanical behaviour of hybrid composites under static loading (Tensile, Shear, Flexural). It is essential to understand the principle that governs the mechanics of composites of laminate under loading which also applicable to hybrid composites C/GFRP. The high modulus fibre, such as Carbon fibre offers stiffness and load bearing capabilities, whereas the low modulus fibre, such as glass fibre makes the composite more durable and low in cost.